Efektivitas Penyelesaian Tindak Pidana Korupsi oleh Jaksa Selaku Penyidik dan Penuntut Umum (Studi Pada Kejaksaan Negeri Kepulauan Morotai) - Andrianto, David; Malik, Faissal; Rumkel, Nam (Jurnal Supremasi, 2024)
This study aims to analyze the effectiveness of prosecutors at the Kepulauan Morotai District Attorney's Office as investigators and public prosecutors in handling corruption cases, as well as to identify the challenges faced during the process. The research employs a normative juridical-empirical method with a sociological law approach, combining secondary data from legal regulations with primary data from field observations. The findings indicate that the Kepulauan Morotai District Attorney's Office has effectively carried out its duties and authorities, as evidenced by its achievements in handling corruption cases from 2020 to 2022. However, several juridical and non-juridical obstacles hinder the resolution of cases. The study implies that further efforts are needed to address these challenges in order to enhance the performance of the District Attorney's Office in the future.